Room temperature curing high temperature resistant thermal protection adhesive, preparation method and application thereof
Patent Information
- Application Number
- CN202611089478.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]现有常温固化热防护胶黏剂主要分为三类,均存在显著局限
(1)制备方法的优势:本发明胶黏剂以NaOH 碱活化、K2SiO3浸渍、Na2B4O7浸渍、TEOS表面偶联与 260℃ 中温热预处理对金云母进行多级化学改性,并以端羟基聚二甲基硅氧烷、聚碳硅烷与纳米 α-Fe2O3两步反应改性有机硅树脂,整套工艺采用三辊研磨、真空行星搅拌等常规设备即可完成;制成胶黏剂涂覆后于 25℃、相对湿度 50% 下静置 24 h 即可完成固化,无需高温烘烤或陶瓷化处理,从根本上克服了「无机硅酸盐/磷酸盐基胶黏剂不能室温固化」等现有技术缺陷,适用于大尺寸、异形构件的现场装配。
Smart Images

Figure CN122898249A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature adhesives, specifically to a room-temperature curing, high-temperature resistant (1200℃) heat-protective adhesive, its preparation method, and its application. This adhesive is mainly used for the assembly, bonding, and interface sealing of high-temperature components such as reusable heat protection components and radomes for reusable rockets. Background Technology
[0002] The thermal protection systems of reusable rockets and reusable spacecraft must undergo a full range of operating conditions, from -55°C to over 1200°C, during multiple reentry operations. This places extremely high demands on the temperature resistance, wide-temperature-range bonding strength, airtightness, and multiple thermal cycle tolerance of the adhesives used to assemble thermal protection components such as ceramic heat insulation tiles, C / C, and C / SiC with the metal load-bearing structure.
[0003] Existing room-temperature curing heat-protective adhesives are mainly divided into three categories, each with significant limitations. The first category consists of silicone-based room-temperature curing adhesives, which have good processability but typically have an upper temperature limit of ≤400℃. The second category comprises inorganic silicate / phosphate-based adhesives, which can withstand temperatures up to 1000–1300℃, but are brittle, have poor thermal shock resistance, and are prone to corroding aerogels. The third category consists of organic / inorganic hybrid adhesives, with a service temperature of 600–1200℃, but exhibit poor high-temperature toughness and cannot meet the sealing requirements under severe vibrations in aircraft.
[0004] In existing related research: (1) The silicone rubber / mica / silica composite system can undergo ceramic transformation and form silicate phase at high temperature (see "Thermal properties and ceramicization mechanism of silicone rubber / mica / silica system", Materials Science, Hans Publishers, 2024), but its effective service temperature is usually only in the range of 600-800℃, and the ceramicization process requires a long time of high temperature treatment, which is difficult to meet the long-term temperature resistance requirement of 1200℃; (2) The 1200℃ temperature resistant ceramic-alloy adhesive developed by institutions such as the Civil Aviation University of China (see China Chemical Industry Information Weekly, November 2023, "New high temperature resistant adhesive can firmly bond ceramics and alloys") has achieved bonding at 1200℃, but its curing temperature is high, it requires high temperature baking ceramicization treatment, and the bonding performance at -55℃ low temperature end and multiple thermal cycle data have not been disclosed, which is difficult to meet the engineering requirements of "room temperature on-site assembly, full temperature range bonding, and multiple thermal cycle resistance" of the recoverable rocket.
[0005] There is an urgent need in this field for a new type of thermal protective adhesive that can simultaneously meet the requirements of room temperature curing, temperature resistance at around 1200℃, reliable bonding across the entire temperature range, high-temperature airtightness, and resistance to multiple thermal cycles. Summary of the Invention
[0006] To address the stringent requirements for adhesives in the assembly of reusable rocket and reusable spacecraft thermal protection systems (room temperature curing, high temperature resistance up to 1200℃, bonding across the entire temperature range, high-temperature airtightness, and multiple thermal cycles), and the common technical contradictions in existing technologies such as insufficient temperature resistance of silicone adhesives, the inability of inorganic adhesives to cure at room temperature and their high brittleness, and performance gaps in the temperature transition zone of hybrid systems, the present invention aims to provide a novel thermal protection adhesive that can cure at room temperature and can operate for extended periods in high-temperature environments up to 1200℃, while maintaining continuous and reliable bonding strength, toughness, and airtightness across the entire temperature range from -55℃ to 1200℃. It is particularly suitable for the assembly and sealing of reusable thermal protection components for reusable rockets, as well as the assembly requirements of similar reusable spacecraft thermal protection systems.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a room-temperature curing, high-temperature resistant heat-protective adhesive, characterized by comprising the following steps: S1. Phlogopite powder was prepared by sequentially performing alkaline activation with sodium hydroxide aqueous solution, impregnation with potassium silicate aqueous solution, impregnation with borax aqueous solution, surface coupling treatment with tetraethyl orthosilicate, and heat pretreatment in air atmosphere at 240–280℃. S2. Hydroxyl-terminated polydimethylsiloxane, polycarbosilane and vinylalkoxysilane are mixed and reacted, and nano-α-Fe2O3 as an antioxidant is added and dispersed evenly to obtain modified organosilicon resin. S3. By weight, mix 80–120 parts of multi-grade modified phlogopite powder, 100 parts of modified organosilicon resin, 5–15 parts of tetraethyl orthosilicate ethanol solution and 1–3 parts of organotin condensation curing catalyst to obtain a room temperature curing, high temperature resistant heat-protective adhesive.
[0008] As a further preferred technical solution of the present invention, S1 specifically includes the following steps performed sequentially: (a) Phlogopite powder was activated in 15–20 wt% NaOH aqueous solution at 95–105 °C for 0.3–1 h; (b) The resulting product was impregnated in 20–40 wt% potassium silicate aqueous solution at 95–105 °C for 1–3 h; (c) The resulting product was impregnated in 20–30 wt% borax aqueous solution at 95–105 °C for 1–3 h; (d) The resulting product was dried and then stirred in an ethanol solution containing tetraethyl orthosilicate (5–15 wt% of the mica mass) at 95–105 °C for 5–15 min; (e) The resulting product was heat-pretreated in air at 240–280 °C for 0.3–1 h; (f) The product was cooled, pulverized, and passed through a 200-mesh sieve.
[0009] More preferably, the temperature of the heat pretreatment in step (e) is 250–260°C and the time is 0.5 h.
[0010] As a further preferred technical solution of the present invention, S2 specifically includes the following steps performed sequentially: (i) Mix 100 parts of hydroxyl-terminated polydimethylsiloxane, 10–20 parts of polycarbosilane and 2–5 parts of vinylalkoxysilane, and react at 120–140 °C for 0.5–1.5 h; (ii) Cool to 95–110 °C, add 3–5 parts of nano-α-Fe2O3, and disperse for 0.5–1.5 h.
[0011] As a further preferred embodiment of the present invention, the viscosity of the hydroxyl-terminated polydimethylsiloxane is 15000–30000 mPa·s; the number-average molecular weight of the polycarbosilane is 1500–2500, and the ceramic yield at 800℃ is not less than 55%; the nano-α-Fe2O3 is of the α-type and has an average particle size of 20–50 nm.
[0012] As a further preferred embodiment of the present invention, the vinylalkoxysilane is vinyltriethoxysilane or vinyltrimethoxysilane. As a further preferred embodiment of the present invention, the organotin condensation curing catalyst is one or more of dibutyltin dilaurate, dibutyltin dioctanoate, and dioctyltin dilaurate.
[0013] According to a second aspect of the present invention, the present invention also provides a heat-protective adhesive, which is prepared by the preparation method described in the first aspect.
[0014] According to a third aspect of the invention, the invention also provides the application of the thermal protective adhesive of the second aspect in the assembly of reusable thermal protective components and radomes for reusable rockets.
[0015] As a further preferred technical solution of the present invention, the adhesive is coated on the surface to be bonded, the adhesive layer thickness is 0.1–0.5 mm, and it is left to cure at 10–40℃ and relative humidity of 20%–80% for 12–48 h; the surface to be bonded is selected from one or more of stainless steel, high temperature alloy, ceramic heat insulation tile, radome substrate, C / C composite material and C / SiC composite material.
[0016] The present invention describes the multi-stage chemical modification mechanism of phlogopite powder. Surface treatment of phlogopite with tetraethyl orthosilicate (TEOS) is a common method to improve the reactivity of fillers in inorganic adhesive systems. After hydrolysis, TEOS generates a large number of silanol groups (≡Si—OH), which can form bridging crosslinks on the mica surface. However, simple conventional "TEOS-mica" coupling modification is difficult to meet the requirements of high-temperature (1200℃) bonding and airtightness. To this end, this invention further introduces potassium silicate (K2SiO3) impregnation and borax (Na2B4O7) impregnation on the basis of TEOS coupling, and is supplemented by medium-temperature heat pretreatment at 240–280℃: Phlogopite is first activated by NaOH alkali, causing partial dissociation of its surface silicon-oxygen network and a significant increase in hydroxyl density (mica surface "hydroxylation"); then the silanol groups introduced by TEOS and potassium silicate condense and dehydrate with the hydroxyl groups on the mica surface at 240–280℃, so that some silicate components are anchored to the mica surface by Si-O-Si bonding, transforming the chemically inert phlogopite into a high-temperature reactive functional filler with a surface rich in reactive groups; borax melts and spreads during high-temperature service (it begins to melt at about 450℃) and covers the filler and adhesive layer surface to form a low-melting-point borosilicate sealing layer, which plays a role in filling gaps, anti-oxidation and gas sealing protection, and can react with the activated mica surface to a certain extent and be pre-fixed during the 240–280℃ heat pretreatment stage. It is the synergistic effect of NaOH activation, TEOS coupling, potassium silicate and borax impregnation, and medium-temperature thermal pretreatment that enables the pre-construction of a Si-O-Si / Si-O-B pre-crosslinked network on the mica surface. (See appendix for a comparison of FT-IR between pristine phlogopite and phlogopite treated with tetraethyl orthosilicate.) Figure 2 The relative enhancement of the characteristic absorptions of silanol and ethoxy groups on the mica surface after treatment, and the downward shift of the Si–O band on the ATR surface, corroborate the coupling of tetraethyl orthosilicate on the mica surface and the improvement of its surface reactivity. The present invention utilizes a continuous relay mechanism for bonding strength across the entire temperature range. In the room temperature to mid-low temperature range, the bonding strength and toughness are primarily provided by an organosilicon elastic network formed by the organotin catalytic condensation of hydroxyl-terminated polydimethylsiloxane. In the mid-temperature transition range (approximately 400–800°C), the ceramic transformation of polycarbosilane (PCS) bridges the performance gaps caused by the pyrolysis of the organosilicon network. In the high-temperature range (800–1200°C), modified phlogopite, silicate, and borate components gradually melt and sinter together with increasing temperature, ultimately forming a silicate-based glass-ceramic network that provides both bonding and airtightness. While using silicate glass phases for high-temperature bonding is a common approach, this invention is characterized by the use of borax (borate) to regulate its melting temperature and spreadability. Since phlogopite and silicate components can withstand approximately 1300°C, the long-term operating temperature limit is set at 1200°C. (See Appendix for the full-temperature range bonding shear strength-temperature curve of Example 1.) Figure 1 ) The antioxidant mechanism of this invention: Nano-α-Fe2O3 in the modified silicone resin acts as a high-temperature antioxidant, which can delay the oxidative degradation of the silicone backbone at high temperatures; the borosilicate sealing layer formed by the melting of borax covers the surface of the adhesive layer, further preventing oxygen from diffusing inward. Borax has a boiling point of approximately 1900℃ and remains stable at 1200℃, therefore the adhesive of this invention still exhibits good antioxidant and airtight properties at 1200℃.
[0017] Compared with the prior art, the present invention can achieve the following beneficial effects: (1) Advantages of the preparation method: The adhesive of the present invention is made by activating NaOH alkali, impregnating K2SiO3, impregnating Na2B4O7, coupling TEOS surface and pre-treating with medium temperature at 260℃ to chemically modify phlogopite in multiple stages, and modifying organosilicon resin by two-step reaction with terminal hydroxyl polydimethylsiloxane, polycarbosilane and nano α-Fe2O3. The whole process can be completed by conventional equipment such as three-roll mill and vacuum planetary stirring. After the adhesive is coated, it can be cured by standing at 25℃ and 50% relative humidity for 24 hours. No high temperature baking or ceramic treatment is required. It fundamentally overcomes the defects of existing technology such as "inorganic silicate / phosphate-based adhesives cannot be cured at room temperature" and is suitable for on-site assembly of large-size and irregularly shaped components.
[0018] (2) Advantages of product characteristics: The adhesive of this invention has a bonding shear strength ≥0.3 MPa in the entire temperature range from -55℃ to 1200℃ (≥3.0 MPa at 25℃ and ≥1.5 MPa at 1200℃, with a second peak in bonding strength at 1200℃); it can withstand 0.1 MPa air pressure for 5 minutes without leakage from room temperature to 400℃, and 0.05 MPa air pressure for 5 minutes without leakage at 1200℃; the high-temperature weight loss rate is ≤9% after holding at 1200℃ for 5 minutes; 30 cycles at 25℃ After a thermal cycle at 1200℃, the shear strength retention rate is approximately 87%. These product characteristics overcome common defects in existing technologies, such as "the temperature resistance of silicone-based adhesives is ≤400℃", "the high brittleness and poor thermal shock resistance of inorganic silicate / phosphate-based adhesives", and "the performance gap in the temperature transition zone of organic / inorganic hybrid systems".
[0019] (3) Advantages of application effect: The adhesive of the present invention is suitable for the assembly, bonding and interface sealing of reusable thermal protection components and radomes of reusable rockets with various substrates such as stainless steel, high temperature alloys, ceramic heat insulation tiles, radome substrates, C / C composite materials, and C / SiC composite materials; its excellent resistance to multiple thermal cycles meets the requirements of reusable spacecraft for multiple reentry and service; the process adaptability of on-site room temperature curing makes it particularly suitable for the on-site assembly of large-size and irregularly shaped thermal protection components, overcoming the engineering bottleneck of the existing solution that "high temperature curing has high requirements for process / equipment and is difficult to assemble on-site". Attached Figure Description
[0020] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0021] Figure 1 This figure shows the adhesive shear strength-temperature curve of the adhesive prepared in Example 1 of the present invention in the full temperature range of -55℃ to 1200℃. The figure visually demonstrates the "relay" characteristic of the adhesive in the full temperature range of -55~400℃, where the high adhesive strength is mainly provided by the organosilicon elastic network, the "transition valley" in the intermediate temperature transition zone of 400~800℃ due to organosilicon pyrolysis and PCS ceramic transformation, the adhesion is mainly undertaken by the mica-silicate-borate glass ceramic network from 800℃, and a secondary adhesive strength peak appears at 1200℃.
[0022] Figure 2 This is a comparison of the Fourier transform infrared (FT-IR) spectra of phlogopite before and after modification in Example 1 of this invention. Curve a represents the original phlogopite, and curve b represents the phlogopite treated with tetraethyl orthosilicate (TEOS) surface coupling. The spectra are displayed at 464 cm⁻¹. -1 The vibration bands of the mica skeleton are normalized based on the reference.
[0023] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0024] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0025] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0026] The various properties of this invention were measured using the following methods: (1) Adhesive shear strength: Refer to GB / T 7124. The bonded body is 1Cr18Ni9Ti stainless steel (or corresponding ceramic heat insulation tile, radome substrate, C / C, C / SiC composite material) specimen, and the adhesive layer thickness is about 0.2 mm. The specimens at room temperature and -55℃ are tested in a universal testing machine. In the high temperature range (400℃, 1000℃, 1200℃), the specimens are placed in a high temperature furnace and heated to the target temperature and held for a period of time before high temperature tensile shear test.
[0027] (2) High-temperature airtightness: Referring to the principle of the liquid coating method (soap film) / pressure drop method for airtightness test in GB / T 12137, the steel pressure-bearing cylinder and air inlet pipe in the test device were replaced with high-temperature resistant alumina ceramic parts (alumina melting point is about 2050℃); the sample heating zone was covered with aerogel insulation material to control the temperature of the sealing zone, and compressed air was introduced through the alumina ceramic tube. The sample was heated to the target temperature (room temperature to 400℃ or 1200℃), and the specified air pressure (0.1 MPa or 0.05 MPa) was applied and held for 5 min. The soap film method / pressure drop method was used to determine whether there was leakage.
[0028] (3) High-temperature weight loss rate: Take a known mass sample and keep it at 1200℃ for 5 min. According to (mass before heat preservation) Calculated as (weight after insulation) / weight before insulation × 100%.
[0029] Example 1 (1) Preparation of multi-stage modified phlogopite powder: Take 100 g of phlogopite powder and activate it in 500 mL of 20 wt% NaOH aqueous solution at 100℃ for 0.5 h (filter and wash with water), soak it in 500 mL of 30 wt% K2SiO3 aqueous solution at 100℃ for 2 h (filter and wash with water), and soak it in 500 mL of 25 wt% Na2B4O7 aqueous solution at 100℃ for 2 h (filter and wash with water). After drying, add 10 wt% of tetraethyl orthosilicate (TEOS, in the form of 20 wt% ethanol solution) equivalent to the mass of mica and stir at 100℃ for 10 min. Transfer it to an oven and pre-treat it in air atmosphere at 260℃ for 0.5 h. After cooling and pulverizing, pass it through a 200-mesh sieve to obtain multi-stage modified phlogopite powder.
[0030] (2) Preparation of modified organosilicon resin: Take 100 parts of 107 silica gel, 15 parts of polycarbosilane (PCS) and 3 parts of vinyltriethoxysilane, react at 130℃ for 1 h under nitrogen protection; cool down to 100℃ and add 3 parts of nano α-Fe2O3, disperse for 1 h to obtain modified organosilicon resin.
[0031] (3) Adhesive preparation and curing: 100 parts of multi-grade modified phlogopite powder, 100 parts of modified silicone resin, 10 parts of tetraethyl orthosilicate (TEOS), and 2 parts of dibutyltin dilaurate (DBTDL) were mixed under vacuum planetary stirring and then milled five times with three rollers to obtain the finished adhesive. Finally, it was coated on the surface of 1Cr18Ni9Ti stainless steel test piece treated with acetone, with an adhesive layer thickness of about 0.2 mm, and cured at 25°C and 50% relative humidity for 24 h.
[0032] Performance testing and structural characterization: Bond shear strength test: Bond shear strength (GB / T 7124) is 3.2 MPa at -55℃, 3.1 MPa at 25℃, 2.7 MPa at 200℃, 2.0 MPa at 400℃, 1.4 MPa at 600℃, 1.0 MPa at 800℃, 1.2 MPa at 1000℃, and 1.7 MPa at 1200℃ (see the full-temperature range bond shear strength-temperature curve). Figure 1 ); Elongation at break at 25℃: 101%; Weight loss at 1200℃ for 5 min: 9%; No leakage at 0.1 MPa air pressure for 5 min from room temperature to 400℃, and no leakage at 0.05 MPa air pressure for 5 min at 1200℃.
[0033] Multiple thermal cycling tests: The adhesive samples prepared in Example 1 were subjected to a thermal cycle of 25℃ → 1200℃ → 25℃ (heating / cooling rate 10℃ / min, holding at 1200℃ for 5 min) for 30 cycles. The results showed that after 30 thermal cycles, the shear strength of the adhesive at 25℃ decreased from 3.1 MPa to 2.7 MPa (retention rate approximately 87%), and the shear strength at 1200℃ decreased from 1.7 MPa to 1.5 MPa (retention rate approximately 88%). There was no leakage even after holding at 0.05 MPa air pressure for 5 min at 1200℃, and the cumulative weight loss at 1200℃ for 5 min was approximately 12%. The adhesive maintained excellent bonding strength and airtightness after repeated reentry-heating-cooling service conditions, demonstrating its good resistance to multiple thermal cycles and meeting the requirements for multiple reentry services of reusable spacecraft.
[0034] To characterize the effects of the aforementioned multi-stage modifications on the surface of phlogopite, Fourier transform infrared (FT-IR) spectroscopy was performed on both pristine phlogopite and phlogopite treated with tetraethyl orthosilicate (TEOS). The results are shown in the appendix. Figure 2 From the appendix Figure 2 It is evident that both the modified and unmodified versions retain the characteristic skeletal vibrational bands of phlogopite, including a band approximately 3618 cm². -1 (Structural hydroxyl O–H stretching), approximately 1080 cm -¹(Si–O–Si antisymmetric stretching), 797 and 779 cm -1 With 518 and 464 cm -1 (Si–O bending vibration), indicating that surface modification did not disrupt the layered silicate structure of the mica matrix; at 464 cm⁻¹ -1 After normalization of the skeletal vibration bands (to eliminate the influence of sample amount differences during tableting), the TEOS-treated phlogopite (curve b) showed a difference in 3400–3450 cm⁻¹ compared to the original phlogopite (curve a). -1 The relative absorption at the (surface / associated hydroxyl O–H stretching) site is significantly enhanced, at 1620 cm⁻¹. -1 Reinforcement at (H–O–H bend) and at 2900–3000 cm - A weak C–H stretching absorption at position ¹, attributable to the ethoxy group (–OC2H5), is observed; in attenuated total internal reflection (ATR) mode, the surface Si–O characteristic band extends from approximately 1024 cm⁻¹. - ¹Moved down to approximately 1004 cm - ¹. The above results show that the hydrolysis and condensation of tetraethyl orthosilicate introduces a silicon-oxygen layer rich in silanol groups (Si–OH) onto the surface of phlogopite, forming a reactive surface layer on the mica surface that can participate in subsequent high-temperature condensation into a network, thus confirming the effectiveness of the coupling treatment of phlogopite surface in this invention.
[0035] Example 2 (NaOH concentration adjusted to 15 wt%) The remaining conditions were the same as in Example 1, except that the NaOH concentration in the multi-stage modified phlogopite powder preparation step was adjusted from 20 wt% to 15 wt%. The resulting adhesive sample had a shear strength of 2.9 MPa at 25°C, a shear strength of 1.5 MPa at 1200°C, a weight loss of 11% at 1200°C, and no leakage after being pressurized in air at 0.05 MPa for 5 min at 1200°C.
[0036] Example 3 (PCS dosage reduced to 10 parts) The remaining conditions were the same as in Example 1, except that the amount of PCS was reduced from 15 parts to 10 parts. The resulting adhesive sample had a shear strength of 3.0 MPa at 25°C, a shear strength of 1.5 MPa at 1200°C, and a weight loss of 11% at 1200°C.
[0037] Example 4 (Amount of nano α-Fe2O3 increased to 5 parts) The remaining conditions were the same as in Example 1, except that the amount of nano-α-Fe2O3 was increased from 3 parts to 5 parts. The resulting adhesive sample had a shear strength of 3.0 MPa at 25°C, a shear strength of 1.8 MPa at 1200°C, and a weight loss of 7% at 1200°C.
[0038] Comparative Example 1 (mica without chemical modification) The remaining conditions were the same as in Example 1, except that the multi-stage modified phlogopite powder was replaced with unmodified phlogopite powder (mechanically pulverized and sieved only). The resulting adhesive sample had a shear strength of 2.8 MPa at 25°C, a shear strength of 0.3 MPa at 1200°C, a weight loss of 25% at 1200°C, and leaked air at 500°C.
[0039] Comparative Example 2 (Silicate and borate impregnation omitted) The remaining conditions were the same as in Example 1, except that the K2SiO3 and Na2B4O7 impregnation steps were omitted during the preparation of the multi-stage modified phlogopite powder. The resulting adhesive sample had a shear strength of 0.6 MPa at 1200℃, a weight loss rate of 18% at 1200℃, and leaked air at 600℃.
[0040] Comparative Example 3 (260℃ heat pretreatment omitted) The remaining conditions were the same as in Example 1, except that the 260℃ / 0.5 h heat pretreatment was omitted when preparing the multi-stage modified phlogopite powder. The resulting adhesive sample had a shear strength of 0.9 MPa at 1200℃ and a weight loss of 15% at 1200℃.
[0041] Comparative Example 4 (without polycarbosilane) The remaining conditions were the same as in Example 1, except that no PCS was added to the modified silicone resin. The resulting adhesive sample had a shear strength of only 0.1 MPa at 500°C, and its elongation at break at 400°C decreased from 21% to 8%.
[0042] The key performance comparison between Examples 1–4 and Comparative Examples 1–4 is shown in Table 1 below.
[0043] Table 1 As shown in Table 1, the shear strength of Examples 1–4 remained at 2.9–3.1 MPa and 1.5–1.8 MPa at 25℃ and 1200℃, respectively, with a weight loss rate of ≤11% at 1200℃. No leakage was observed when the air pressure was maintained at 0.05 MPa for 5 minutes at 1200℃. This indicates that by adjusting the NaOH concentration, PCS, and nano α-Fe2O3 dosage within the process range defined by this invention, the adhesive still meets the requirements for bonding in the entire temperature range and high-temperature airtightness. Among them, Example 1 is the formulation with the best overall performance.
[0044] The comparative analyses are as follows: Comparative Example 1 (mica without chemical modification): The shear strength at 1200℃ dropped sharply from 1.7 MPa in Example 1 to 0.3 MPa, the weight loss rate increased from 9% to 25%, and air leakage occurred at 500℃. This confirms that multi-stage chemical modification of mica is the core to achieving high-temperature bonding and airtightness. Comparative Example 2 (without potassium silicate and borax impregnation) showed a shear strength of only 0.6 MPa at 1200℃, a weight loss rate of 18%, and air leakage at 600℃, indicating that the silicate / borate component is indispensable for bonding strength above 1000℃ and high-temperature airtightness. Comparative Example 3 (omitting the 260℃ heat pretreatment) showed a shear strength of 0.9 MPa, a weight loss of 15%, and an air tightness reduction to 0.03 MPa at 1200℃, indicating that medium-temperature heat pretreatment is necessary for locking the inorganic pre-crosslinked network on the mica surface. Comparative Example 4 (without polycarbosilane) showed a shear strength of only 0.1 MPa at 500℃ and an elongation at break of 8% at 400℃, indicating that PCS is irreplaceable for the bonding continuity in the intermediate temperature transition zone.
[0045] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.
Claims
1. A method for preparing a room-temperature curing, high-temperature resistant heat-protective adhesive, characterized in that, Includes the following steps: S1. Phlogopite powder was prepared by sequentially performing alkaline activation with sodium hydroxide aqueous solution, impregnation with potassium silicate aqueous solution, impregnation with borax aqueous solution, surface coupling treatment with tetraethyl orthosilicate, and heat pretreatment in air atmosphere at 240–280℃. S2. Hydroxyl-terminated polydimethylsiloxane, polycarbosilane and vinylalkoxysilane are mixed and reacted, and nano-α-Fe2O3 as an antioxidant is added and dispersed evenly to obtain modified organosilicon resin. S3. By weight, mix 80–120 parts of multi-grade modified phlogopite powder, 100 parts of modified organosilicon resin, 5–15 parts of tetraethyl orthosilicate ethanol solution and 1–3 parts of organotin condensation curing catalyst to obtain a room temperature curing, high temperature resistant heat-protective adhesive.
2. The preparation method of the room temperature curing, high temperature resistant heat-protective adhesive according to claim 1, characterized in that, S1 specifically includes the following steps performed sequentially: (a) Phlogopite powder was activated in 15–20 wt% NaOH aqueous solution at 95–105 °C for 0.3–1 h; (b) The resulting product was immersed in a 20–40 wt% potassium silicate aqueous solution at 95–105 °C for 1–3 h; (c) The obtained product was impregnated in a 20–30 wt% aqueous solution of borax at 95–105 °C for 1–3 h; (d) After drying, the product was stirred at 95–105 °C for 5–15 min in an ethanol solution containing tetraethyl orthosilicate (5–15 wt% of mica by weight); (e) The resulting product was pretreated in air at 240–280 °C for 0.3–1 h; (f) The resulting product is cooled, pulverized, and passed through a 200-mesh sieve.
3. The method for preparing the room-temperature curing, high-temperature resistant heat-protective adhesive according to claim 2, characterized in that, The heat pretreatment in step (e) is performed at a temperature of 250–260 °C for 0.5 h.
4. The method for preparing the room-temperature curing, high-temperature resistant heat-protective adhesive according to claim 1, characterized in that, S2 specifically includes the following steps performed sequentially: (i) Mix 100 parts of hydroxyl-terminated polydimethylsiloxane, 10–20 parts of polycarbosilane and 2–5 parts of vinylalkoxysilane, and react at 120–140 °C for 0.5–1.5 h; (ii) Cool to 95–110℃, add 3–5 parts of nano α-Fe2O3, and disperse for 0.5–1.5 h.
5. The method for preparing the room-temperature curing, high-temperature resistant heat-protective adhesive according to claim 1 or 4, characterized in that, The viscosity of the hydroxyl-terminated polydimethylsiloxane is 15,000–30,000 mPa·s; and / or the number-average molecular weight of the polycarbosilane is 1,500–2,500, and the ceramic yield at 800℃ is not less than 55%; and / or the nano-α-Fe2O3 is of the α-type with an average particle size of 20–50 nm.
6. The method for preparing the room-temperature curing, high-temperature resistant heat-protective adhesive according to claim 1 or 4, characterized in that, The vinylalkoxysilane is one or both of vinyltriethoxysilane and vinyltrimethoxysilane.
7. The method for preparing the room-temperature curing, high-temperature resistant heat-protective adhesive according to claim 1, characterized in that, The organotin condensation curing catalyst is one or more of dibutyltin dilaurate, dibutyltin dioctanoate, and dioctyltin dilaurate.
8. A heat-protective adhesive, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The application of the thermal protective adhesive of claim 8 in the assembly of reusable thermal protective components and radomes for reusable rockets.
10. The application according to claim 9, characterized in that, The adhesive is applied to the surface to be bonded, with a thickness of 0.1–0.5 mm, and cured statically for 12–48 h at 10–40°C and 20%–80% relative humidity; the surface to be bonded is selected from one or more of stainless steel, high-temperature alloy, ceramic heat insulation tile, radome substrate, C / C composite material and C / SiC composite material.